Validation of Psychometric Instrumentswith Classical Test Theory in Social and Health Sciences: A practical guide - López-Pina, Jose-Antonio; Veas, Alejandro (Anales de Psicología / Annals of Psychology, 2024)
In recent years there has been a significant rise in the number of psychometric studies, together with crucial statistical advances for validity and reliability measures. Given the importance of providing accurate procedures both in methodology and score interpretation of tests and/or measurement scales, the editors-in-chief of the journal Annals of Psychology have drafted this guide to address the most relevant issues in the field of applied psychometry. To this end, the present manuscript analyses the main topics under the Classical Test Theory framework (e.g., exploratory/confirmatory factor analysis; reliability, validity, bias, etc.) aiming to synthesize and clarify the best practical applications, and improve publication standards.